Bizanțul în filtrul balcanic – poezie română din a doua jumătate a secolului XX / Byzantium in Balkanic filter – Romanian poetry in the second part of twentieth century - Darabus, Carmen (Swedish Journal of Romanian Studies, 2020)
Talking about Balkanism in Romanian contemporary poetry means to betray, to a certain extent required by degradation or alteration, some literary themes and motifs. Finding ourselves in a geographical area of cultural contaminations, the influence of other peoples in Balkans comes naturally: the nostalgia of Byzantium perfection, continuous reporting at an ideal time, abstraction of the chronology. Balkan themes and motives in poetry are identifiable from the early writings of Romanian literature, including the folklore, with Anton Pann, the Vacarescu and Conachi poets – and their ludic descriptivism – , to Ion Barbu, who strikes a metaphysical note in the Balkan motifs, and later, in the second part of twentieth century, with the species of parody. The Romanian native receptivity allowed continuous assimilations without creating an unpleasant heterogeneous feeling. This openness has contributed decisively in a formative way to bring Byzantium on a new soil in a perfect and saturated array; the perfectibility is not possible anymore, so the failure was natural, in a degraded status – Constantinople. Oriental-Byzantine gravity becomes in Oriental-Balkan tragedy or comedy, balance slid to one extreme, sometime becoming ridiculous. Contemporary poetry does not express any more a true lament, but a kind of parody (in ludic poetry) or sheer contempt (in the solemn poetry). The Balkan intelligence is not critical, but creative, with the risk of perpetuating monstrous forms, beyond good and evil. Byzantium established itself through a double filter – for the East and for the West – influencing and being influenced, in turn. Romanian poetry has the full sequence of themes and aesthetic formulae, from tragic to comic, often switching rapidly from one edge to the other, taking into account the old Thracian solemn part, then the proud Byzantium and its absorption in Constantinople – all rolling in a series of formal expressions reflected in themes and vocabulary.